2018
DOI: 10.1063/1.5044479
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of water-worked and screeded gravel beds: A comparative study

Abstract: The turbulence characteristics within flows over water-worked gravel beds (WGBs) and screeded gravel beds (SGBs) were examined by measuring the instantaneous flow velocity field using a two-dimensional particle image velocimetry system. To compare the responses of a WGB and an SGB to velocity and various turbulence characteristics, the flow Froude number was kept identical for both the beds that remained immobile. The roughness structures of both the beds were measured using a laser scanner. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…In their study, owing to the water action, the WGB roughness structure was observed to be better organized than the SGB roughness structure, where gravels were randomly sorted. Akin to other rough-flow, in the study by Padhi et al [32], owing to the presence of gravels, the values of ū in both the WGB and SGB are small in the near-bed flow zone. However, they gradually increase with an increase in vertical distance, reaching a maximum at the free surface.…”
Section: Effects Of Water-work On Streamwise Velocitymentioning
confidence: 76%
See 3 more Smart Citations
“…In their study, owing to the water action, the WGB roughness structure was observed to be better organized than the SGB roughness structure, where gravels were randomly sorted. Akin to other rough-flow, in the study by Padhi et al [32], owing to the presence of gravels, the values of ū in both the WGB and SGB are small in the near-bed flow zone. However, they gradually increase with an increase in vertical distance, reaching a maximum at the free surface.…”
Section: Effects Of Water-work On Streamwise Velocitymentioning
confidence: 76%
“…However, they gradually increase with an increase in vertical distance, reaching a maximum at the free surface. Moreover, Padhi et al [32] found that, close to the bed, the ū in the WGB is higher than that in the SGB, although the flow conditions in both the beds were alike. They argued that the well-organized roughness structure in a WGB makes the near-bed flow more streamlined than that in an SGB, inducing the ū to attain a higher magnitude in the former than in the latter.…”
Section: Effects Of Water-work On Streamwise Velocitymentioning
confidence: 98%
See 2 more Smart Citations
“…The bed surface topography and the flow characteristics in water-worked and screeded gravel beds were explored by several researchers [1,[5][6][7][8][9][10][11][12]. However, a series of recent studies by Padhi et al [13][14][15] indicated a clear distinction in turbulence characteristics in water-worked and screeded gravel bed flows. Therefore, the research on water-worked beds, in addition to the related hydrodynamics and transport processes, being the topic of this Special Issue, demands further attention.…”
mentioning
confidence: 99%